Elevated serum glutathione peroxidase levels reducing the risk of acute upper gastrointestinal bleeding combined with acute coronary syndrome: Evidence from observational, interventional, and Mendelian randomization studies - Weibo Zhang; Hailing Zhang (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Acute upper gastrointestinal hemorrhage (UGIH) combined with acute coronary syndrome (ACS) poses a significant clinical challenge linked to oxidative stress, while elevated serum glutathione peroxidase (GSH-Px) levels may provide a protective effect. Methods: A two-phase study was conducted. First, Mendelian randomization (MR) analysis using three GSH-Px-associated SNPs (rs6993770, rs1097234, rs4149991) was performed to assess causality between genetically predicted GSH-Px activity and UGIH-ACS risk, leveraging public GWAS data. Second, a randomized, double-blind, placebo-controlled trial (RCT) enrolled UGIH-ACS patients (n = 110) to received oral selenium (200 μg/day) or placebo for 8 weeks. Comparisons were made with a UGIH-only control group (n = 78) and healthy controls (n = 83). Serum GSH-Px levels, 90-day mortality, rebleeding rates, and major adverse cardiovascular events (MACE) were analyzed. Results: MR analysis showed no significant causal link between GSH-Px activity and UGIH-ACS risk (IVW OR: 0.966, 95 % CI: 0.873–1.069, p = 0.502), but the weighted median method suggested a marginal protective trend (OR: 0.958, 95 % CI: 0.918–1.000, p = 0.048). Sensitivity analyses confirmed robust estimates with low heterogeneity. In the RCT, selenium supplementation significantly increased GSH-Px levels (+51.9 % vs. +6.0 %, p < 0.001), reduced 90-day rebleeding (12.0 % vs. 22.7 %, p = 0.014), and lowered MACE risk (9.1 % vs. 21.8 %, p = 0.042). Conclusion: While MR analysis found no strong causal link between GSH-Px activity and UGIH-ACS risk, the weighted median method indicated a marginal protective trend, underscoring GSH-Px's role in oxidative stress modulation. Selenium supplementation significantly increased GSH-Px activity (+51.9 %, p < 0.001), reduced rebleeding, and lowered MACE risk, supporting its potential as adjunctive therapy for UGIH-ACS and warranting further investigation into additional mechanisms.